Quality assessment of ksub0-NAA by statistical evaluation of CRM results - Bučar, Tinkara (Acta chimica slovenica, 2008)
The k0-based neutron activation analysis (k0-NAA) is an analytical method basedon nuclear properties of atoms. Since it is a multi-element technique, correlations among repeated measurement results for different elements can in principle be observed in case of certain systematic errors. For a deeper insight into potential sources of uncertainty and potential systematical errors of the analytical method, a set of measurement results for the StandardReference Material (SRM) 2782 obtained from the National Institute forStandards and Technology (NIST) was analyzed using standard statistical approach. The measurements results were examined over an extended period of time to obtain reproducibility of the method. Correlations of repeated measurements among several elements, although dispersions are small, were indeed observed, and the origin of the correlations as the potential source ofuncertainty is discussed. A comparison of the measurements with the NIST SRM2782 reference values was made to benchmark the k0 NAA setup at the TRIGA Mark II reactor of the Jo ef Stefan Institute and proved the overall accuracy of the method. The article is focused on the possible sources of the correlations of the measurement results and not on the uncertainty of the method itself.
Keywords: kemija okolja; nevtronska aktivacijska analiza